2013
DOI: 10.1093/trstmh/trt063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trichomonas vaginalis and risk factors in women treated at public health units in Brazil: a transversal study

Abstract: Although there are programs to control other sexually transmitted diseases, there are none for trichomoniasis. The results of this study indicate the presence of T. vaginalis in the female population, and points to the need for more research in Brazil to gain a better understanding of the profile and epidemiology of the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
16
1
3
Order By: Relevance
“…Infection with T. vaginalis has also been associated with variables such as age [21], smoking [18], and use of hormonal contraceptives [42]. In our study, however, there was no association between positive results for T. vaginalis and any of these variables.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Infection with T. vaginalis has also been associated with variables such as age [21], smoking [18], and use of hormonal contraceptives [42]. In our study, however, there was no association between positive results for T. vaginalis and any of these variables.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of T. vaginalis in each age group depends on several factors, including the technique used to assess this prevalence [17][18][19][20]. For example, research using culture, wet mount, and Pap smear found a prevalence of 2.6% in women attending primary health clinics in Uberlândia, MG, in the southeast region of Brazil [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vaginalis infection among non-pregnant women (1.4%) was lower than the rates observed in other studies of non-pregnant females aged 12 to 52 years conducted in Ceará (4.1%) [31]; São Paulo, SP (3.2%) [32]; and Minas Gerais (2.6%) [33]. In contrast, the prevalence of T .…”
Section: Discussionmentioning
confidence: 60%
“…Studies in Latin America revealed similar prevalence values of 7.6% in Argentina 47 7.8% in Chile 48 and 9.1% in Peru 49. In Brazil, prevalence ranged from 2.6% to 20% among women 50515253 and the Health Ministry estimates a general prevalence of 15% 54. These uncertain data are due to the limitations in sample selection, since it is not representative of the Brazilian population in general.…”
Section: Trichomoniasis In Numbersmentioning
confidence: 92%